The aid of panoramic photo for a general practitioner for denture preparation - Herawanti YE; Isidora KS; Sarianoferni .; Setyowati O; Sujati . (Makassar Dental Journal PDGI Makassar, 2018)
Radiographic photo imaging nowadays is needed in almost all areas of health. Faculty of Dentistry students at Hang Tuah University had to accomodate competence-based curriculum (CBC) to face the new horizon in oral health care. This present study presents an older woman, 71 years old who wanted to make a partial denture, both upper and lower jaws. She had ever used a partial denture since about 2 years ago. She felt discomfortable and wanted to make a new one. She was healthy in her age, with no systemic deviation, and she works as a teacher. The management of the case taking her anamnesis, taking the panoramic photo to overview all of the condition in the mouth. With the help of the imaging, continue the preparation of the teeth beside the edentulous areas for the clasps and the mucosa to bare the dentures. Several teeth were treated conservatively. This is important for designing the denture. By applying the CBC, the student was able to wholly treat the patient, just like the competence that hopefully possessed by all of the dentists nowadays. The CBC allows students to make a panoramic photo, to treat conservative, to apply medicine and to screen from the systemic disease, curing the gingiva, or any other else. It was concluded that the CBC students was able to apply all the competences to patients. The CBC students have to fully understand and work hard to carry out their obligations. Hopefully, this condition will prepare them to compete in the era of globalization.